Evaluating the Effectiveness of ACT for Anxiety Disorders in a Self-Help Context: Outcomes From a Randomized Wait-List Controlled Trial. Issue 4 (July 2016) - Ritzert, Timothy R.; Forsyth, John P.; Sheppard, Sean C.; Boswell, James F.; Berghoff, Christopher R.; Eifert, Georg H.
Abstract: Rigorous evaluations of cognitive behavioral self-help books for anxiety in pure self-help contexts are lacking. The present study evaluated the effectiveness of an Acceptance and Commitment Therapy (ACT) self-help workbook for anxiety-related concerns, with no therapist contact, in an international sample. Participants ( N  = 503; 94% mental health diagnosis) were randomized to an immediate workbook ( n  = 256) or wait-list condition ( n  = 247). Assessments at pretreatment, 12 weeks, 6 months, and 9 months evaluated anxiety and related symptoms, quality of life, and ACT treatment processes (e.g., psychological flexibility). Participants in the wait-list arm crossed over to the workbook following the 12-week assessment. The workbook condition yielded significant improvements on all assessments from pre- to posttreatment relative to wait-list, and these gains were maintained at follow-ups. The pattern observed in the wait-list condition was virtually identical to the active treatment arm after receiving the workbook, but not before. Attrition was notable, but supplemental analyses suggested dropout did not influence treatment effects for all but one measure. Overall, findings provide preliminary support for the effectiveness of this self-help workbook and suggest ACT-based self-help bibliotherapy might be a promising low-cost intervention for people experiencing significant anxiety-related concerns. Highlights: An international sample ( N  = 503) was provided ACT self-help workbooks for anxiety A wait-list crossover treatment design was used, with no therapist contact Workbook use produced improvements in anxiety, quality of life, and ACT processes Outcomes were replicated in the wait-list group following crossover to treatment All improvements were maintained at follow-up assessments